2017
DOI: 10.1053/j.ajkd.2016.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Additives and Albuminuria in Early Stages of CKD: A Randomized Controlled Trial

Abstract: Background Little is known about the effects of phosphorus additives on patients with kidney disease. Study Design Randomized, double-blind, cross-over trial Setting & Participants 31 adults with early stages of presumed chronic kidney disease (estimated glomerular filtration rate [eGFR] ≥ 45 ml/min/1.73m2; urine albumin-creatinine ratio [ACR] sex-specific cut points: men ≥ 17 mg/g, women ≥ 25 mg/g). Intervention Higher vs lower phosphorus intake for 3 weeks. Higher phosphorus intake was achieved by addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In fact, under normal physiological conditions, a healthy kidney is able to regulate urinary secretions of phosphates with food intake, but the progressive loss of glomerular filtrate, due to CKD progression, rationalizes a reduction of phosphorus intake to below 700 mg/die, the recommended level for the general adult population [ 36 ]. Surely, it is useful to educate patients to avoid consuming “hidden” phosphates through additives found in preserved foods or soft drinks [ 38 , 39 ]. Choosing foods with a lower phosphorus content and using foods of plant origin is useful in limiting the net phosphorus load [ 40 ].…”
Section: Considering the Physiopathology Of Advanced Chronic Renal Inmentioning
confidence: 99%
“…In fact, under normal physiological conditions, a healthy kidney is able to regulate urinary secretions of phosphates with food intake, but the progressive loss of glomerular filtrate, due to CKD progression, rationalizes a reduction of phosphorus intake to below 700 mg/die, the recommended level for the general adult population [ 36 ]. Surely, it is useful to educate patients to avoid consuming “hidden” phosphates through additives found in preserved foods or soft drinks [ 38 , 39 ]. Choosing foods with a lower phosphorus content and using foods of plant origin is useful in limiting the net phosphorus load [ 40 ].…”
Section: Considering the Physiopathology Of Advanced Chronic Renal Inmentioning
confidence: 99%
“…However, the effect of phosphorus intake on FGF23 appears to be modest in human studies, with some studies unable to detect a significant effect (19, 32, 48, 78, 79, 94, 111, 161, 165). Recent human studies suggest that PTH rather than FGF23 explains the increased phosphaturia that occurs immediately after an acute phosphorus load (137).…”
Section: Phosphorus Metabolism In Healthmentioning
confidence: 99%
“…Chang et al (32) recently conducted a randomized, crossover study examining the effects of phosphorus additives on urinary albumin excretion in 31 patients with eGFR ≥45 mL/min/1.73 m 2 and albuminuria. Participants received unaltered, commercially available diet beverages and breakfast bars with and without phosphorus additives to produce a contrast of 998 mg/d of dietary phosphorus and 505 mg/d in 24-h urine phosphorus excretion between periods.…”
Section: Effects Of Dietary Phosphorus Intake On the Kidneymentioning
confidence: 99%
“…The biggest reason between the former studies [23,24,25] and the latter studies [13], including our study, is that the former studies [23,24,25] have shown that phosphorous intake is associated with the risk of ESRD exacerbations and death in most of the patients with stage 3 or higher CKD; whereas the latter studies have shown that phosphorous intake is associated with the likelihood of CKD morbidity in the general population, where CKD patients with three or more stages are less common (about 25% [mean age = 65 years] or 15% [mean age = 66 years] in two Italian studies [13] and only 1.8% in the Korean population [this study]). Due to the complex interaction between FGF23 [26], phosphorus metabolism [9], and CKD progression [27], further studies exploring the relationship between dietary phosphorus and CKD are needed.…”
Section: Discussionmentioning
confidence: 99%